Exploring AMR and virulence in Klebsiella pneumoniae isolated from humans and pet animals: A complement of phenotype by WGS-derived profiles in a One Health study in Egypt - Enas A. Soliman; Alaa Saad; Ashraf A. Abd El Tawab; Fatma I. Elhofy; Amira M. Rizk; Manar Elkhayat; Tamara Kozytska; Majdil Ilyas; Marwa Bassiouny; Hanka Brangsch; Mathias W. Pletz; Heinrich Neubauer; et al. (One Health)
Klebsiella pneumoniae is a ubiquitous nosocomial pathogen associated with various types of infections in hospitalized patients and different animal species. In the current study, 49 Klebsiella strains isolated from humans, dogs, and cats were investigated using NGS technology. MALDI-TOF failed to identify newly discovered K. variicola and K. quasipneumoniae isolates correctly. MLST analysis revealed different sequence types among K. pneumoniae isolates, and the most frequent STs were ST29, ST219, and ST37. Three ST23 that are generally known as hypervirulent type were identified but they lacked major discriminatory determinants for hypervirulent K. pneumoniae (hvKp). K. pneumoniae isolates showed high diversity, and several isolates from humans and animals were assigned to the same ST and were almost identical. Isolates from humans exhibited more pronounced resistance patterns compared to the animal isolates. High levels of resistance were observed for piperacillin, trimethoprim/sulfamethoxazole, and cephalosporins, and resistance to carbapenem compounds was only found in isolates of human origin. Three strains of human origin were extensively drug-resistant (XDR). A diverse range of resistance genes primarily confer resistance to beta-lactams., phenicol/quinolone, aminoglycoside, macrolide, sulfonamides, and fosfomycin were identified in silico. However, there were inconsistencies between the phenotypic characterization of isolates and the set of resistance genes detected in silico in this set of Klebsiella isolates. Further research using a larger number of isolates from various sources is necessary to fully comprehend the relationship between the presence of antimicrobial resistance determinants and phenotypic data. It is also necessary to monitor the spread of K. pneumoniae from a One Health perspective in Egypt.